STRATEGI MAHASISWA BIMBINGAN DAN KONSELING TINGKAT AKHIR ANGKATAN 2022 UNIVERSITAS SLAMET RIYADI DALAM MENGATASI TEKANAN PENYUSUNAN SKRIPSI DITINJAU DARI TIPE KEPRIBADIAN MBTI FEELING (F) DAN THINKING (T) TAHUN 2026 - Yunita, Nelly; Heru Sri Suryanti, Hera; Adi Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Nelly Yunita STRATEGIES OF FINAL-YEAR GUIDANCE AND COUNSELING STUDENTS CLASS OF 2022 SLAMET RIYADI UNIVERSITY IN COPING WITH THESIS WRITING PRESSURE REVIEWED FROM MBTI PERSONALITY TYPES FEELING (F) AND THINKING (T) IN 2026 :The aim of this research was to determine the strategies of final-year Guidance and Counseling students class of 2022 at Slamet Riyadi University in coping with thesis writing pressure reviewed from MBTI personality types Feeling (F) and Thinking (T). The research method used was descriptive qualitative method. The subjects of this research were final-year Guidance and Counseling students class of 2022 who were in the process of writing their thesis. The research instruments used were observation guidelines, interviews and documentation employed in the data collection process with subjects. The data obtained were then analyzed through several stages such as summarizing, concluding, and verification. Based on the results of data analysis, it was found that students with MBTI Feeling (F) personality type and students with MBTI Thinking (T) personality type have different strategies in coping with thesis writing pressure. This can be seen from MBTI Feeling (F) students who tend to seek emotional validation from closest people and Thinking (T) students who focus on solutions.